Properties and in vivo investigation of nanocrystalline hydroxyapatite obtained by mechanical alloying - Silva, C. C.; Pinheiro, A. G.; de Oliveira, R. S.; Goes, J. C.; Aranha, N.; de Oliveira, L. R.; Sombra, ASB (Elsevier B.V., 2004)
Mechanical alloying has been used successfully to produce nanocrystalline powders of hydroxyapatite (HA) using three different procedures. The milled HA was studied by X-ray diffraction, Infrared, Raman scattering spectroscopy and Scanning Electron Microscopy (SEM). We obtained HA with different degrees of crystallinity and time of milling. The grain size analysis through SEM and XRD shows particles with dimensions of 36.9, 14.3 and 35.5 nm (for (R1), (R2) and (R3), respectively) forming bigger units with dimensions given by 117.2, 110.8 and 154.4 nm (for (R1), (R2) and (R3), respectively). The Energy-Dispersive Spectroscopy (EDS) analysis showed that an atomic ratio of Ca/P= 1.67, 1.83 and 1.50 for reactions (R1), (R2) and (R3), respectively. These results suggest that the R1 nanocrystalline ceramic is closer to the expected value for the ratio Ca/P for hydroxyapatite, which is 513 congruent to 1.67. The bioactivity analysis shows that all the samples implanted into the rabbits can be considered biocompatible, since they had been considered not toxic, bad not caused inflammation and reject on the part of the organisms of the animals, during the period of implantation. The samples implanted in rabbits had presented new osseous tissue formation with the presence of osteoblasts cells. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: investigation; nanocrystalline hydroxyapatite; mechanical alloying